2021
DOI: 10.1177/13675494211017911
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS and its monsters. Negotiating criminalisation along the monster–human continuum

Abstract: We use the concept of the ‘monster’ in this article as an analytical tool to grasp a variety of persons who – understood to be criminals in their countries of residence, and living with or thought to be particularly vulnerable to HIV – are perceived as threats from across the European region. Building on the field of monster studies, we focus here on strategies undertaken to shift the ‘monstrous’ towards the ‘human’ along what we describe as monster–human continuums. Relying on ethnographic fieldwork from Germ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The COVID-19 pandemic has again brought to the front the realization that it is socially and economically vulnerable groups who are most affected during an epidemic, and that the demonization or monsterization (Dziuban et al, 2021) of particular communities in a folk way identified as the agents or "carriers" of the virus/disease (for HIV/AIDS -gay men, sex workers or people who use drugs, and for COVID-19 -people who "look Asian," paramedics or animals), runs along a violent, survivalist logic unhinged from scientific or medical findings. In his "Queer Epidemics" contribution to this issue, Tomasz Sikora elaborates on the logics of social exclusion and immunization, cultural dynamics of epidemics, and fear of contagion.…”
mentioning
confidence: 99%
“…The COVID-19 pandemic has again brought to the front the realization that it is socially and economically vulnerable groups who are most affected during an epidemic, and that the demonization or monsterization (Dziuban et al, 2021) of particular communities in a folk way identified as the agents or "carriers" of the virus/disease (for HIV/AIDS -gay men, sex workers or people who use drugs, and for COVID-19 -people who "look Asian," paramedics or animals), runs along a violent, survivalist logic unhinged from scientific or medical findings. In his "Queer Epidemics" contribution to this issue, Tomasz Sikora elaborates on the logics of social exclusion and immunization, cultural dynamics of epidemics, and fear of contagion.…”
mentioning
confidence: 99%